2016
DOI: 10.1038/boneres.2016.37
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-specific demethylase 1 inhibitor rescues the osteogenic ability of mesenchymal stem cells under osteoporotic conditions by modulating H3K4 methylation

Abstract: Bone tissue engineering may be hindered by underlying osteoporosis because of a decreased osteogenic ability of autologous seed cells and an unfavorably changed microenvironment in these patients. Epigenetic regulation plays an important role in the developmental origins of osteoporosis; however, few studies have investigated the potential of epigenetic therapy to improve or rescue the osteogenic ability of bone marrow mesenchymal stem cells (BMMSCs) under osteoporotic conditions. Here, we investigated pargyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 48 publications
4
40
0
Order By: Relevance
“…It has been reported that interventions entailing H3K4 modification may hold promise for the prevention of osteoporosis. Certain inhibitors of H3K4 demethylases were reported to upregulate H3K4 methylation at the osteogenesis-related genes in BMSCs of osteoporotic mice, thus promoting the osteogenic capability of BMSCs and rescuing bone loss [39,40]. In our research, both in vitro and ex vivo, we found that Ash1l promotes C3 cells osteogenesis.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It has been reported that interventions entailing H3K4 modification may hold promise for the prevention of osteoporosis. Certain inhibitors of H3K4 demethylases were reported to upregulate H3K4 methylation at the osteogenesis-related genes in BMSCs of osteoporotic mice, thus promoting the osteogenic capability of BMSCs and rescuing bone loss [39,40]. In our research, both in vitro and ex vivo, we found that Ash1l promotes C3 cells osteogenesis.…”
Section: Discussionsupporting
confidence: 53%
“…These findings are consistent with previous reports. In one relevant study, the total level of H3K4me3 was markedly decreased in BMSCs of OVX mice [39]. In Ras-induced senescence of IMR90 cells and in the astrocytes of aging rats, researchers detected a lower level of H3K4me3 compared with their counterparts [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using in vivo collagen scaffolds infused with hASCs implanted subcutaneously in nude mice showed that scaffolds with LSD1‐knockdown hASCs exhibited increased density and ossification compared with scrambled controls . Further, treatment with the LSD1 inhibitor pargyline helped restore the osteogenic capacity of ex vivo expanded BMSCs from aged osteoporotic mice and/or OVX mouse models . Our results demonstrated that MM cocultured with BMSCs enhanced the recruitment of LSD1 to epigenetically suppress Runx2 expression and the differentiation potential of OB progenitors .…”
Section: Epigenetic Targeting As Treatment Of Mmbdmentioning
confidence: 67%
“…Several studies reported that LSD1 inhibits osteogenic and supports adipogenic differentiation . LSD1 inhibitors, pargyline and CBB1007, have been shown to enhance alkaline phosphatase activity and extracellular matrix mineralization by hASCs without apparent cellular toxicity . Further analysis showed that LSD1i rescued osteogenic differentiation by enhancing the dimethylation level of H3K4 at the promoter regions of osteogenesis‐related genes .…”
Section: Epigenetic Targeting As Treatment Of Mmbdmentioning
confidence: 99%
See 1 more Smart Citation